2012
DOI: 10.2527/jas.2011-4306
|View full text |Cite
|
Sign up to set email alerts
|

Feeding corn during the last 12 days of gestation improved colostrum production and neonatal activity in goats grazing subtropical semi-arid rangeland1

Abstract: The objectives were to investigate if partial substitution of a grazing diet with a supplemental high-starch feed during the last 12 d of gestation improved colostrum yield and neonatal activity in goat does grazing semi-arid rangeland. For the first objective, 25 pregnant does were randomly assigned to 1 of 2 treatments: 1) grazing only (control; n = 11), and 2) grazing plus 0.6 kg/d of supplemental corn (as fed), a high starch feed, during the last 12 ± 1.0 d before parturition (SC; n = 14). Colostrum was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
9
0
2
Order By: Relevance
“…Improvement in the maternal behaviour in mothers in the maize group of this study may be partially due to the level of neonatal activity displayed by their kids. In fact, feeding maize during late pregnancy in goats that graze extensively improved neonatal activity (high frequency for udder seeking, sucking, and LPB emission) after birth (Ramírez-Vera et al, 2012). This improved kid behaviour could make them more attractive for mothers, thus reinforcing the display of maternal care towards more active neonates, as proposed by Klopfer and Klopfer (1977).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Improvement in the maternal behaviour in mothers in the maize group of this study may be partially due to the level of neonatal activity displayed by their kids. In fact, feeding maize during late pregnancy in goats that graze extensively improved neonatal activity (high frequency for udder seeking, sucking, and LPB emission) after birth (Ramírez-Vera et al, 2012). This improved kid behaviour could make them more attractive for mothers, thus reinforcing the display of maternal care towards more active neonates, as proposed by Klopfer and Klopfer (1977).…”
Section: Discussionmentioning
confidence: 91%
“…Under these conditions, many lambs die of starvation as they do not receive adequate colostrum, but supplementing these females with maize during late gestation increased the amount of colostrum available for the newborn at birth (Banchero et al, 2004a,b;Murphy et al, 1996). Recently we have reported that feeding corn during the late gestation improved colostrum production and neonatal activity in goats grazing subtropical semi-arid rangeland (Ramírez-Vera et al, 2012). Therefore, in parturient goats under poor grazing conditions this increase of colostrum production and the improved kid activity due to the inclusion of maize in the diet probably promote the early formation of mother-young bond.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to the nutritional and immunological benefits, colostrum in the gut improves the ability of the newborn to recognize its mother and thus contributes to the establishment of the mother-young bond (Goursaud and Nowak, 1999;Ramírez-Vera et al, 2012a). With the implementation of restricted, brief mating periods and ultrasound assessment of pregnancy, focus feeding can be used in the last week of gestation to increase greatly the amount of colostrum available at birth (review: Banchero et al, 2006) and improve neonatal survival (Goodwin and Norton, 2004;Ramirez-Vera et al, 2012b).…”
Section: Maximize Colostrum Productionmentioning
confidence: 99%
“…In turn, not only milk production and offspring development will be compromised [10], but also an increased offspring mortality rate would be expected [1,2,11]. Furthermore, such a depressed physiological scenario will also negatively affect the doe-offspring behavioral interactions and bonding while it will depress the newborn strength [5,12]. To overcome such a physiological demanding scenario is not only essential for kid survival but also to safeguard the newborn cognitive competence and recognizing ability [5,13].…”
Section: Introductionmentioning
confidence: 99%